ANALISIS FINANSIAL USAHA TERNAK AYAM PROBIOTIK : STUDI KASUS: KPA BERKAT USAHA BERSAMA, KOTA METRO - Bayu Suci C. Sunarya; Zainal Abidin; Umi Kalsum (Lampung University, 2016)
This research aims to determine the financial feasibility of probiotic chickens farming, and analyze the sensitivity of the feasibility of probiotic chickens farming at KPA Berkat Usaha Bersama in the event of price increases in DOC, feed, and decrease of production. This research is a case study at KPA Berkat Usaha Bersama at Village of Yosomulyo 21, District of Metro Center, in Metro City. KPA Berkat Usaha Bersama was selected on purpose as the research location. The data was taken from June to July 2015. The number of sample were 23 chicken farmers and 1 chairman of KPA Berkat Usaha Bersama. The analytical tool used NPV, Net B / C Ratio, Gross B / C ratio, IRR, Payback Period, ROI, the sensitivity analysis was also used in this study. The results showed that with 1000 birds population of probiotic chickens farming could generate net income Rp1.008.098 per season and the results of the financial analysis using six criteria for investment in probiotic chickens farming was feasible and profitable. The value of NPV was Rp53.613.075,93, Net B/C Ratio was 1,41, Gross B/C Ratio was 1,02, IRR was 24 percent, PP was 1,04 years, and ROI was 48 percent. In the event of a decrease production in the amount of 5 percent and an increase in feed prices by 6 percent, the feasibility and profitability of probiotic chickens farming could affect these changes. However, in case of DOC price increase of 6 percent, the feasibility and profitability had no effect on these changes. It could be concluded that the probiotic chickens farming at KPA Berkat Usaha Bersama was feasible to be developed, but if there is a change in feed prices by 6 percent, and if there is a decrease in production by 5 percent, the feasibility and profitability of probiotic chickens farming could affect these changes.Key words: financial analysis, probiotic chickens farming, sensitivity